POLITIC GOES DIGITAL, SO WHAT? A REVIEW ON INTERNET POLITICS - Irmawan Rahyadi (Business Economic, Communication, and Social Sciences (BECOSS) Journal, 2019)
This article explores and mobilises the concept of ‘internet politics’ as an analytical entry point for understanding how politics emerge in the digital media world targeted to the public conversation and constituents believe to promote engagement and participation. Understanding political communication to public in digital platform is strategic in a digital era where exposure to political message is inevitable. Some leading academic databases are searched within a methodology of literature review to report a review of studies on internet politics. The result shows that research in this area incline towards utilization of a specifc platform in digital world. We conclude that political communication in the digital world started in the west and followed by non-western researcher. Technological advancement makes possible for people to communicate and gather virtually as in social media platform, thus any digital platform accessible for a substantial number of people is a potential channel for political communication where further research in this area needs to be directed.